The influence of change in business environment on change in the adoption and use of management control system : a study of Libyan small and medium size privatized firms pre and post-privatization / Yosef Kalefa Hosen - Hosen, Yosef Kalefa (2013)
This study utilizes the contingency theory approach to investigate the contingent relationships between change of several contextual factors (intensity of competition, business strategy, information technology and national culture) and change in adoption and use of management control systems (MCS) among small and mediumsize firms during the pre and post-privatization periods in the Libyan context. It also investigates the relationship between change in adoption and use of MCS and change in firm performance. This study also seeks to develop a wider and more comprehensive view of adoption and use of MCS among small and medium size firms. This study fills the gap between theory and practices of MCS by testing the change in adoption and use of MCS over time, pre and post-privatization. To achieve the objectives, the study employed the mixed method. First, quantitative data were collected through a survey during which 178 managers (81% response rate) answered a questionnaire. Next, qualitative data were obtained from 19 managers in two case studies for insights into how and why MCS has changed. The findings revealed that there was a change in the adoption and use of MCS, pre and post-privatization, and the highest rate of adoption and use of MCS postprivatization was in the financial and planning sub-system, suggesting that traditional financial accounting and budgeting have a strong position in small and medium-size firms . To examine the relationship between change in the business environment and change in the adoption and use of MCS, six hypotheses were tested. Four hypotheses were supported, and two rejected. Therefore, the change in the adoption and use of MCS are associated with the effect of change in several factors related to intensity of competition, change in business strategy and change in IT. The results also imply that there is a relationship between change in the adoption and use of MCS and change in firm performance. Data were collected through interviews with managers suppot1ed the results that emerged from the quantitative study. The finding contribute to the body of management control system knowledge by identifying change in adoption and use of MCS among small and medium size firms and investigating the relationship between adoption and use of MCS and firm performance.